2012
DOI: 10.1017/s0714980812000360
|View full text |Cite
|
Sign up to set email alerts
|

End of Life in Residential Care from the Perspective of Care Aides

Abstract: RÉSUMÉNous avons examiné les caractéristiques contextuelles qui façonnent les soins de fin de vie (SFV) dans les établissements de soins pour bénéficiaires, en s’appuyant sur les perspectives de 11 aidants résidents (AR) dans un centre urbain canadien de l’Ouest. ARs décrivent les soins de fin de vie comme “offrant un confort,” y compris le bien-être physique et émotionnel. Les inquiétudes au sujet des défis posés par le temps et la charge de travail ont dominé les comptes et ont généré la culpabilité, la tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Consequently, a sub-study was undertaken, aiming to better understand staff's grief experience and to identify their perceived support needs (Marcella & Kelley, 2015). The findings, similar to that of the research by Waskiewich, Funk, and Stajduhar (2012), indicated that the UCP's experiences with loss and grief are complex, much shaped by the emotional impact of each loss, the cumulative burden of ongoing grief, and the organizational culture in LTC. The study identified several recommendations, among them the implementation of organizational procedures to support staff dealing with loss and grief, the implementation of organizational strategies and rituals to acknowledge all residents who die in the LTC home, and supporting staff with time and resources to reach out to colleagues after the death of a resident to acknowledge their loss and grief.…”
Section: Context and Methods Of The Researchsupporting
confidence: 79%
See 3 more Smart Citations
“…Consequently, a sub-study was undertaken, aiming to better understand staff's grief experience and to identify their perceived support needs (Marcella & Kelley, 2015). The findings, similar to that of the research by Waskiewich, Funk, and Stajduhar (2012), indicated that the UCP's experiences with loss and grief are complex, much shaped by the emotional impact of each loss, the cumulative burden of ongoing grief, and the organizational culture in LTC. The study identified several recommendations, among them the implementation of organizational procedures to support staff dealing with loss and grief, the implementation of organizational strategies and rituals to acknowledge all residents who die in the LTC home, and supporting staff with time and resources to reach out to colleagues after the death of a resident to acknowledge their loss and grief.…”
Section: Context and Methods Of The Researchsupporting
confidence: 79%
“…Whether it be discussing details about the resident's death, what they need to do to begin closure or what they need from each other, the attention paid to the needs of the staff are seen as a vital intervention. Waskiewich et al (2012) support this process through their research, noting the importance of emotional processing as it links to an opportunity for closure following a resident's death. While it is the relationship between the UCP and resident that creates quality end-of-life care, it is this very relationship that must be addressed when this relationship ends through death.…”
Section: Peer Support Debriefing As An Intervention To Mitigate Disenmentioning
confidence: 94%
See 2 more Smart Citations
“…The qPAD(Long et al, 2012) with its specificity for evaluating knowledge of advanced dementia precludes a more generalised knowledge and need for skills in a palliative approach when caring for cognitively intact older people who may voice their existential concerns at end of life(Waskiewich et al, 2012). The Comfort Scale (Nochomovitz et al, 2010) administered as an audio questionnaire offers an initiative for participants for whom understanding the written English language may be difficult.…”
mentioning
confidence: 99%